Karakteristik Mineral Pembawa Pasir Besi Daerah Pantai Pancana Kabupaten Barru Provinsi Sulawesi Selatan: Characteristics of Iron Sand Carrying Minerals in Pancana Beach Area, Barru Regency, South Sulawesi Province - Zulfadli, Zulfadli; Nawir, Alfian; Harwan, Harwan; Bakri, Suriyanto (Journal of Engineering Science and Technology Applications, 2024)
Iron sand is one of the industrial minerals. The utilization of iron sand in Indonesia is still limited to being used as a raw material for cement factories in the manufacture of concrete. Iron is given the symbol (Fe) in the periodic table's chemical element. The purpose of this study was to determine the mineral properties of iron sand and the chemical characteristics of iron sand. The research location is in the Barru district in the province of South Sulawesi, Indonesia. This research method uses XRD and XRF analysis methods. From the results of the XRD analysis, it was found that 2 minerals carrying iron sand, including the minerals Magnetite and Hematite with the percentage content of these minerals, are. Magnetite mineral (Fe3O4) 9,3% and Hematite mineral (Fe2O3) 0,3%. The results of XRF analysis show that the chemical composition contained in F2O3 minerals, containing oxide and hydroxide elements Fe, O, and Oxide, is a chemical compound that contains at least one oxygen atom and at least one other element.